Early diagnosis of the hemodynamic regulation disorders in orthostasis - I. D. Martynov (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The article deals with the informative content of spectral analysis of heart rate variability in the assessment of the regulatory impacts on the systemic hemodynamics during orthostatic test. It was observed that the patients who suffer from neurogenic syncope already at a young age had had a decrease in low frequency oscillations, as well as a decrease in peripheral vascular resistance during the test. It allows us to make a conclusion about the sympathetic vasomotor regulation dysfunction, even before the symptoms of orthostatic hypotension were evident. The decrease in the tonic vagal effect which follows from the depression of high-frequency oscillations, makes for increasing the chronotropic function of the heart and keeps a relative sympathetic predominance in order to maintain adequate level of blood pressure.